2021
DOI: 10.6007/ijarbss/v11-i11/11650
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing The Intention to Adopt eWallet among Students of Universiti Putra Malaysia

Abstract: This research is aimed to investigate the factors influencing student's intention to adopt eWallet in Universiti Putra Malaysia. A total of 200 students from Universiti Putra Malaysia participated in this research where they were chosen through simple random sampling method and systematic sampling method. Data were collected through self-administered questionnaires. Categorical scale and five-point Likert scale were applied to analyze the background of respondents, as well as to measure the independent and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…In addition, perceived ease of use (β=--0.004, p=0.926) indicated that for every 1 unit increase in perceived ease of use, the behavioral intention to use (BIU) e-wallet among UiTM Melaka students will decrease by 0.004 units. Because it had the highest regression coefficient (=0.523) and was similar to the finding made by Osman et al (2021), who found that perceived usefulness was the greatest influencing factor towards students at UPM's intention to adopt an electronic wallet because it had the highest regression coefficient (=0.612), we can conclude from these results that students at UiTM Melaka believed perceived usefulness to be the most significant factor affecting their behavioural intention to use an electronic wallet.…”
Section: Correlation Analysissupporting
confidence: 85%
See 4 more Smart Citations
“…In addition, perceived ease of use (β=--0.004, p=0.926) indicated that for every 1 unit increase in perceived ease of use, the behavioral intention to use (BIU) e-wallet among UiTM Melaka students will decrease by 0.004 units. Because it had the highest regression coefficient (=0.523) and was similar to the finding made by Osman et al (2021), who found that perceived usefulness was the greatest influencing factor towards students at UPM's intention to adopt an electronic wallet because it had the highest regression coefficient (=0.612), we can conclude from these results that students at UiTM Melaka believed perceived usefulness to be the most significant factor affecting their behavioural intention to use an electronic wallet.…”
Section: Correlation Analysissupporting
confidence: 85%
“…Karim et al (2020) found that perceived usefulness, perceived ease of use, and privacy are additional important factors to consider when analyzing behavioral intentions to use an e-wallet. Osman & Yi (2021) in their findings indicated that intention to use an e-Wallet among UPM students was positively correlated with perceived usefulness, perceived ease of use, and perceived security while perceived usefulness stood to be the most significant factor. It showed that the UPM students have the highest intention to use e-wallets.…”
Section: Literature Review E-wallets Usementioning
confidence: 90%
See 3 more Smart Citations